PERANCANGAN MEDIA INTERAKTIF MENGENAL NAMA – NAMA HEWAN DAN TUMBUHAN UNTUK ANAK USIA DINI - RAHMAT FITRA ANANDA, Drs. M. Nasrul Kamal, M.Sn, Drs. Ariusmedi, M.Sn (DEKAVE : Jurnal Desain Komunikasi Visual, 2014)
Interactive media recognize the names of animals and plants showing various kinds of animals and plants. Presented in the form of images and text. The process of delivering to children early age assisted by mentor teachers or parents. This certainly requires to be able to attract the attention of children and tried to optimize the delivery of information in interactive media is to be well understood. Based on the these problems, the authors will design a teaching media to recognize the names of animals and plants that displays several images of animals and plants which also include with audio of animal sounds.and audio elements that combined in this media is expected to achieve the goal of designing the interactive media. The purpose of the interactive media design itself is how to how to make the delivery of information could be optimal and may increase the existence and independence of early childhood in recognizing about animals and plants through the interactive media.The design method of this interactive media using SWOT analysis. Strength (strength) from the interactive media that will be designed, weakness (weakness) from media recognize the names of animals and plants which is graphical, opportunity (opportunities) as seen from the data of observation, and Threat (threat) found from the data of observation results. The consideration is due to SWOT analysis is used to assess and re-assess (reevaluation) something that has existed and already decided previously with the goal of minimizing the risks that may arise.Design results of interactive media recognize the names of animals and plants are packed in a CD along with the design of the cover and the cover of the CD. Where information is packaged in the form of recognize names of animals and plants, and a quiz to guess the names of animals.keywords : interactive media, early childhood, Animals name, plants name